(untitled) (Applied Biological Research, 2024)
Drosophila species (fruit flies) have long served as valuable model organisms in evolutionary research. Among the diverse traits exhibited by fruit flies, cold tolerance stands out as a critical factor influencing their ecological distribution and survival in varied environments. The majority of research on cold tolerance concentrates on subjecting flies to a single, stressful temperature without any modulation in the diet. The present study aimed to understand the impact of nutrient-specific modulation on the cold tolerance of Drosophila ananassae and D. bipectinata across a broad range of lower temperatures. Adult flies were transferred to the media composition enriched with sucrose and tryptophan in three replicates and maintained at 22oC. 20 flies of a particular stage: adults, eggs, larvae and pupa were exposed to 18oC, 14oC, and 10oC for 5 days. The impact of cold stress on their growth and survival was noted for 5 following days. The impact of dietary modifications on cold stress tolerance and life history traits was positive and consistent across both species. In contrast, D. bipectinata had greater survival rates than D. ananassae across all temperatures and dietary regimes. Tryptophan (100 mg) diet performed best to improve life traits on cold stress treatment.